Low-Level Laser Therapy and Calcitonin in Bone Repair: Densitometric Analysis - Tatiana Pinto Ribeiro; Simone Bustamante Nascimento; Claúdia Alessandra Cardoso; Raduan Hage; Janete Dias Almeida; Emilia Angela Loschiavo Arisawa (International Journal of Photoenergy)
The aim of this work was to evaluate the association of low-level laser therapy (LLLT, 830 nm) and calcitonin in bone repair considering that bone healing remains a challenge to health professionals. Calcitonin has antiosteoclastic action and LLLT is a treatment that uses low-level lasers or light-emitting diodes to alter cellular function. Both are used to improve bone healing. Densitometry is a clinical noninvasive valuable tool used to evaluate bone mineral density (BMD). Sixty male rats were submitted to bone defect with a trephine bur, randomly divided into four groups of 15 animals each: control (C); synthetic salmon calcitonin (Ca); LLLT (La); LLLT combined with calcitonin (LaCa). Animals from Ca and LaCa received 2 UI/Kg synthetic salmon calcitonin intramuscularly on alternate days after surgery. Animals from groups La and LaCa were treated with infrared LLLT (830 nm, 10 mW, 20 J/cm2, 6 s, contact mode). Five animals from each group were euthanized 7, 14, and 21 days after surgery and bone defects were analyzed by densitometry. Statistical analysis showed a significant difference in BMD values in LaCa group at 7 and 21 days (𝑃=0,005). The results of the densitometric study showed that LLLT (830 nm) combined with calcitonin improved bone repair.